Modern Solutions to Measures Aimed at Reducing the Perinatal Risk of Premature Birth - Nosirov Umidjon Zokir o'g'li; Ikromova Parvina Khamidjon qizi (Journal of Science in Medicine and Life, 2024)
This concept in medicine of risk groups during pregnancy is necessary to minimize the possibility of developing complications that can lead to premature birth and congenital pathologies during pregnancy. During this period, ultrasound examination during pregnancy includes determining the condition of the placenta and the intensity of blood flow, the development and mobility of the fetus, its position (appearance of the head or pelvic organs), the presence of malformations and the estimated weight. is a fetus. Sometimes mothers-to-be who are at risk need to be admitted to a day hospital, so that doctors can monitor them for 6-8 hours a day, provide the necessary medical care and perform some procedures.